Mengenal Pertanian Sejak Dini Pada PAUD Mutiara Hati Palm Spring Keluharan Jambangan Surabaya - Mahrus Ali; Nurlina; Nurul Huda; Yeni Ika Pratiwi; Soiman (Universitas Merdeka Surabaya, 2023)
Agricultural education at an early age is very important because considering that today's children tend to be minimal, therefore learning about agriculture starts from around the world in order to produce capable farmers and become professional experts in the field of agriculture. The introduction of agricultural education must be implemented from an early age in children, so that it creates a love for the surrounding environment. One of them is using the school yard to always look beautiful, beautiful and attractive by cultivating various kinds of horticultural and other commodities. One of them is the introduction of vegetable plants, which aims to increase students' awareness of the environment by providing illustrations of the impact of planting on the environment. The results of this service have had a positive impact on PAUD Mutiara Hati Palm Spring students, providing additional knowledge on how to cultivate vegetables.